Digital Civic Engagement and Policy Misinformation: Hoax Narratives of Indonesia’s Free Nutritious Meal Program - Muhamad Handar; Lidwina Hana; Purbowo Purbowo (Jogjakarta Communication Conference (JCC), 2026)
The rapid expansion of digital media ecosystem has accelerated the circulation of misinformation surrounding public policies. In Indonesia, one policy that has recently become the subject of online misinformation is the Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG), a national initiative aimed at improving children’s nutritious and strengthening human capital development. While existing studies on misinformation largely focus on political elections and health crises, limited research has examined misinformation narratives related to welfare and food policy. This study analyzes the characteristics and framing of hoax narratives related to the Free Nutritious Meal Program and explores their implication for digital civic engagement. The research employs a qualitative approach using qualitative content analysis and framing analysis. Data were collected from fact-checking archive of TurnBackHoax, managed by the Indonesian Antihoax Society (Mafindo). Using the keyword “makan bergizi gratis,” the dataset consists of 30 verified hoax cases published between 2024 and 2026. The analysis examines narrative structures, content typologies, and dissemination patterns of misinformation across digital platforms. This research contributes to the study of policy misinformation by highlighting how hoax narratives shape public perceptions of food policy and proposes a policy-based hoax literacy approach to strengthen digital civic engagement and public information resillience.